World Economic Outlook, April 2017 : Gaining Momentum?. (World Economic Outlook; World Economic Outlook ;, 2018)
Global economic activity is picking up with a long-awaited cyclical recovery in investment, manufacturing, and trade, according to Chapter 1 of this World Economic Outlook. World growth is expected to rise from 3.1 percent in 2016 to 3.5 percent in 2017 and 3.6 percent in 2018. Stronger activity, expectations of more robust global demand, reduced deflationary pressures, and optimistic financial markets are all upside developments. But structural impediments to a stronger recovery and a balance of risks that remains tilted to the downside, especially over the medium term, remain important challenges. Chapter 2 examines how changes in external conditions may affect the pace of income convergence between advanced and emerging market and developing economies. Chapter 3 looks at the declining share of income that goes to labor, including the root causes and how the trend affects inequality. Overall, this report stresses the need for credible strategies in advanced economies and in those whose markets are emerging and developing to tackle a number of common challenges in an integrated global economy.